Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1121/1.1446052
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of an aeroacoustic dipole using a linear microphone array

Abstract: It is shown that the standard beamformer technique is inadequate for both the source location and the measurement of a simple dipole and that this is due to the assumption of monopole propagation in the calculation of the phase weights used to steer the focus of the array. A numerical simulation is used to illustrate the problem and to develop a correction to the signal processing algorithm to account for the dipole propagation characteristic. This is then applied to array measurements for an aeroacoustic dipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The technique of Jordan et al [16], however, is not applicable in the case of a distribution of dipoles because their directivities and hence the required corrections vary over the source region, unlike the case of a single dipole. We do not have access to the source code for array analysis software to modify the algorithm for a distribution of axial dipoles.…”
Section: Motivation Of Theoretical Simulationmentioning
confidence: 99%
See 3 more Smart Citations
“…The technique of Jordan et al [16], however, is not applicable in the case of a distribution of dipoles because their directivities and hence the required corrections vary over the source region, unlike the case of a single dipole. We do not have access to the source code for array analysis software to modify the algorithm for a distribution of axial dipoles.…”
Section: Motivation Of Theoretical Simulationmentioning
confidence: 99%
“…Jordan et al [16] has shown that the standard beamforming technique is inadequate for both the source location and the measurement of a simple dipole, and that this is due to the assumption of monopole propagation in the calculation of the phase weights used to steer the focus of the array. They developed a correction to the beamforming algorithm to account for the dipole propagation characteristics, and applied it to array measurements for an aeroacoustic dipole produced by a cylinder in a cross flow.…”
Section: Motivation Of Theoretical Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…We found an example of beamforming on directional sources in two papers where the sources are aeroacoustic dipoles [Jordan 2002] [Liu 2008]. The authors were interested in finding the locations of the dipoles.…”
Section: Christian Bouchardmentioning
confidence: 99%